Sales Transaction Analysis at Barokah Minimarket With the Implementation of the Apriori Algorithm - Ardi Wijaya; Muhammad Rifqo; A.R. Walad Mahfuzhi; Prayoga Putra (Penerbit Jurnal Indonesia, 2025)
Minimarket Barokah is a minimarket located in Rafflesia Hospital, Bengkulu City. Minimarket Barokah is owned by the Rafflesia Hospital Foundation Bengkulu. The sales focus or target market targeted by Minimarket Barokah is visitors from Rafflesia Hospital, families of patients, and employees of the hospital. Data mining, often also called knowledge discovery in database (KDD), is an activity that includes collecting, using historical data to find regularities, patterns or relationships in large data sets. The output of data mining can be used to improve future decision making. Apriori algorithm is the most famous algorithm for finding high frequency patterns. The Apriori algorithm can be used in the sales process by providing a correlation between sales data, in this case the food or drinks purchased will get a consumer purchase pattern. The minimarket can use this information to take actions that increase profits for the minimarket owner. It is expected that the barokah minimarket always updates transaction data gradually so that this application can provide sales information based on stock to the leadership